2021
DOI: 10.3389/fnins.2021.664410
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic-Induced Specific Oscillations in the Medial Prefrontal Cortex to Reverse Propofol Anesthesia

Abstract: General anesthesia is a drug-induced reversible state comprised of altered states of consciousness, amnesia, analgesia, and immobility. The medial frontal cortex (mPFC) has been discovered to modulate the level of consciousness through cholinergic and glutamatergic pathways. The optogenetic tools combined with in vivo electrophysiological recording were used to study the neural oscillatory modulation mechanisms in mPFC underlying the loss of consciousness (LOC) and emergence. We found that optogenetic activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…Although data from this study and previous reports 18 , 19 provide compelling evidence that the basal forebrain is an arousal-promoting area, we cannot discount the possibility that—rather than being a source of arousal, per se—the basal forebrain may be a point of convergence for the arousal-promoting influence of other subcortical nuclei and/or that the basal forebrain may be activating other brain regions to promote behavioral arousal. For example, selective activation of orexinergic terminals in basal forebrain was shown to accelerate the emergence from isoflurane anesthesia, 36 and orexin administration in basal forebrain has been shown to increase cortical acetylcholine and facilitate recovery from anesthesia.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Although data from this study and previous reports 18 , 19 provide compelling evidence that the basal forebrain is an arousal-promoting area, we cannot discount the possibility that—rather than being a source of arousal, per se—the basal forebrain may be a point of convergence for the arousal-promoting influence of other subcortical nuclei and/or that the basal forebrain may be activating other brain regions to promote behavioral arousal. For example, selective activation of orexinergic terminals in basal forebrain was shown to accelerate the emergence from isoflurane anesthesia, 36 and orexin administration in basal forebrain has been shown to increase cortical acetylcholine and facilitate recovery from anesthesia.…”
Section: Discussioncontrasting
confidence: 73%
“…Luo et al 18 showed that genetic lesions of basal forebrain cholinergic neurons delayed the emergence from isoflurane and propofol anesthesia, while chemogenetic stimulation of basal forebrain cholinergic neurons had an opposite effect. In a similar and more recent study, Wang et al 19 demonstrated that optogenetic stimulation of cholinergic and glutamatergic neurons in basal forebrain accelerated the emergence from propofol anesthesia. Although the results from these 2 studies and our findings from the current study converge, it is important to note that, unlike facilitating passive emergence from anesthesia as was done in past studies, we were able to actively reverse the state of general anesthesia (in the continued presence of sevoflurane) and provide the most robust evidence for a direct role of basal forebrain cholinergic neurons in promoting behavioral arousal and emergence from anesthesia.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our findings suggest that DBS of CT might help restore not only arousal but also awareness in patients with disorders of consciousness, as previously investigated in some patients ( 37 , 43 ). While previous studies demonstrated that direct modulation of other cortical ( 62 ) and subcortical ( 63 65 ) brain areas could reverse the anesthesia-induced loss of consciousness in rodent models, there was no evidence that it could also restore conscious access. Nevertheless, a clear limitation of our experiment is that it relies on a primate model of loss of consciousness due to anesthetic agents ( 18 , 45 , 46 ).…”
Section: Discussionmentioning
confidence: 96%
“…To determine how to modulate the propofol process by changing glutamatergic neuron activity, local field potentials and cortical EEG were used to analyze the relationship between glutamatergic neuron and propofol. Wang found that cortical EEG and field potential during propofol anesthesia changed from a low‐frequency, high‐amplitude slow‐oscillating pattern to an active high‐frequency, low‐amplitude pattern as a result of glutamatergic neuron activation in the BF 41 . All of these transmitter and electrophysiological studies suggest that glutamatergic neurons in BF play a role in the regulation of anesthesia.…”
Section: The Role Of Bf In General Anesthesiamentioning
confidence: 99%